Lu-177-PSMA dosimetry for kidneys and tumors based on SPECT images at two imaging time points - Chen, Gefei; Lu, Zhonglin; Jiang, Han; Afshar-Oromieh, Ali; Rominger, Axel; Shi, Kuangyu; Mok, Greta S. P. (Frontiers in Medicine, 2023)
Background: Personalized dosimetry for Lu-177-PSMA treatment requires multiple-time-point SPECT/CT scans to calculate time-integrated activity (TIA). This study evaluates two-time-point (TTP) methods for TIA calculation for kidneys and tumors. Methods: Eighteen patients treated with 3.7-7.4 GBq Lu-177 PSMA-617 were analyzed retrospectively, including 18 sets of left and right kidneys as well as 45 tumors. Four quantitative SPECT/CT (4TP) were acquired at 2 h, 20 h, 40 h, 60 h (n=11) or 200 h (n=7) after treatment, and they were fit bi-exponentially as reference. TTP method was fitted by a mono-exponential washout function using 2 selected imaging time points for kidneys. For tumors, 1 uptake and 1 washout phase were modeled, assuming linear (type I) and same (type II) uptake phase between 0 h to the first time point, and mono-exponential washout afterwards. Two single-time-point (STP) methods were also implemented for comparison. TIA calculated by TTP and STP methods were compared with reference 4TP TIA. Results: For kidneys, the TTP methods using 20 h-60 h and 40 h-200 h had smaller mean absolute errors of 8.05%±6.05% and 4.95%±3.98%, respectively as compared to other combinations of time points and STP methods. For tumors, the type I and type II TTP method using 20 h-60 h and 40 h-200 h had smaller mean absolute errors of 6.14%±5.19%, 12.22%±4.44% and 8.31%±7.16% and 4.48%±7.10%, respectively as compared to other TTP and STP methods. Conclusion: TTP method based on later imaging time demonstrated less errors than STP methods in both kidney and tumor TIA. Imaging at 20 h-60 h and 40 h-200 h could simplify the dosimetry procedures with less TIA estimation errors.